Pengaruh Permainan Olahraga Tradisional Bakiak Terhadap Kemampuan Motorik Kasar Di UPTD SD 145 Barru - M. Asri B (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study focuses on the gross motor skills of children who have not developed as expected. This study aimed to determine how traditional clog games affect children's gross motor skills at UPTD SDN 145 Barru. This study uses a descriptive experimental type. To collect data, observation sheets, interviews, and documentation were used. The results of the analysis of children's gross motor skills before being given traditional clog game activity treatment showed that In the BSB category, in the BSH category, in the MB category, and in the BB category. After the traditional clog game activity was given, the BSB category reached the BSH category, the MB category, and the BB category. Furthermore, percentage techniques and t-tests were used to manage the data. The t-count value ≥ t-count, which means greater, according to the results of the t-test calculation. The results showed that H0 was rejected and H1 was accepted, so traditional clog game activities influenced children's gross motor skills.